cot2 A - cos2 A = cot2 A × cos2 A
Asked by akbarreshma123 | 24th Oct, 2020, 08:35: PM
Please check the steps below.
cot2A - cos2A
This gives RHS.
Answered by | 26th Oct, 2020, 09:41: AM
- sec²a.cosec²a = tan²a + cot²a+ 2
- (sin A+ cos A) (sec A+ cosec A) = 2+sec A.cosec A
- prove that 3(sinA-cosA)^⁴+6(sinA+cosA)^²+(sin^⁶A+cos^⁶A)=14
- Prove that √1+cosø/1 -cosø + √1-cosø/1+cosø = 2cosecø
- tan^2 a - sin^2 a =
- 1st question please solve it !
- prove that: sin^3/cosA + sinAcosA = tanA
- prove that: (sinA + cosecA)^2 + (cosA + secA)^2 = 7 + tan^2A + cot^2A
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number